Press Release from the California Democratic Delegation - Dick Kline:::::: (1968)
A press release from the California Democratic Delegation announces that Assembly Speaker Jesse M. Unruh appointed 154 Californians as alternates to the Democratic National Convention. Under convention rules, California is entitled to 174 delegates and 172 alternates, with 18 additional alternates to be appointed shortly. Unruh also noted that two female delegates, Mrs. Gladys Danielson and Mrs. Sara J. Hannaford, resigned in favor of their husbands, State Senator George Danielson and Mayor Mark W. Hannaford. The release lists dozens of newly appointed alternates from Los Angeles County. It also provides an extensive list of alternates from other regions throughout California.